Using information technology : - Sawyer, Stacey C. (Irwin/McGraw-Hill, 1999)
This book is very well written and simple to read. I know quite a bit about computers and how fast things change with them. I also have many friends and family who have a wide range in knowledge when it comes to computers. I find it very amazing how much information is packed into this book and how simple it allows a person to "learn" while reading. You can choose particular topics to learn more about, or just read the entire book for an all around greater understanding of computers and electronics